Reproducibility of concentric and eccentric isokinetic strength of the knee flexors in elite volleyball players - Dauty, M.; Rochcongar, P. (Isokinetics and Exercise Science, 2001)
The aim of this study is to define the test-retest reproducibility for measuring the peak torque of the knee flexors according to the isokinetic concentric and eccentric muscle action. The tests were done in two sessions at a 21 day interval. Ten healthy national-level volleyball players, 24.3 years old - 3.9 were included. Tests took place after the competition season. Evaluation was carried out with a Cybex 6000 dynamometer and the reliability was calculated according to the intra-class correlation coefficient (ICC~2.1). The protocol consisted of 5 isokinetic concentric contractions at 180°/s followed by 5 isokinetic eccentric contractions at 30 and 60°/s. Results show an excellent reproducibility for isokinetic concentric peak torque at 180°/s. (ICC: 0.94) and very good reproducibility for isokinetic eccentric peak torque at 30 and 60°/s. (ICC: 0.86; 0.83). These results indicate that knee flexion strength at these velocities may be used to estimate the performance of volleyball players.